2013
DOI: 10.1113/jphysiol.2013.259747
|View full text |Cite
|
Sign up to set email alerts
|

The role of myogenic mechanisms in human cerebrovascular regulation

Abstract: Key points• The autoregulatory capacity of the cerebral vasculature allows for maintenance of relatively stable blood flow in the face of fluctuating arterial pressure to protect neural tissue from wide swings in oxygen and nutrient delivery.• We recently found that neurogenic control plays an active role in autoregulation. Although myogenic pathways have also been hypothesized to play a role, previous data have not provided an unequivocal answer.• We examined cerebral blood flow responses to augmented arteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(100 citation statements)
references
References 42 publications
3
92
1
Order By: Relevance
“…The precise mechanisms of CA remain largely controversial (11,457), and might vary from dynamic to static metrics, and from increases and decreases in MAP. Nonetheless, it is generally accepted that CA in general is mediated by the integration of metabolic, myogenic, and neurogenic factors (438,439,475). The evidence of these factors in the regulation of human CA have been recently reviewed (456 (475) (Fig.…”
Section: Cerebral Autoregulationmentioning
confidence: 99%
“…The precise mechanisms of CA remain largely controversial (11,457), and might vary from dynamic to static metrics, and from increases and decreases in MAP. Nonetheless, it is generally accepted that CA in general is mediated by the integration of metabolic, myogenic, and neurogenic factors (438,439,475). The evidence of these factors in the regulation of human CA have been recently reviewed (456 (475) (Fig.…”
Section: Cerebral Autoregulationmentioning
confidence: 99%
“…[5][6][7] In healthy young individuals the cerebral microcirculation is uniquely protected by the proximal resistance arteries of the circle of Willis and the pial arterial network, which contribute significantly to moment-to-moment regulation of cerebrovascular resistance. 8 In addition to their well-characterized role in steadystate myogenic autoregulation of cerebral blood flow (CBF; reviewed in the study by Tan et al 9 ), myogenic response of these arteries also plays a central role in dampening of pulse pressure waves, protecting the downstream microcirculation from pressure-induced injury (reviewed in the study by Vrselja et al 10 ). Although increasing evidence from clinical 4,11 and experimental studies 12,13 suggest that aging may impair local vasoregulatory mechanisms, age-related alterations in myogenic adaptation of cerebral arteries to pulsatile pressure remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the energy density of IMF6 and IMF7 decreases owing to the domination of Mayer wave, which is consistent to the change in LF and VLF in conventional BPV. The other intrinsic fluctuations of ABP are regulated by sympathetic nervous system, such as the changes in the peripheral resistance (0.05-0.2Hz), or regulated by the temperature regulation (0.01-0.05Hz) [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Lots of clinical BPV studies investigated that each frequency band indicated different neurohumoral systems mechanisms involved in non-stationary dynamic auto-regulation. Very low frequency fluctuations (VLF, 0.01-0.04Hz) indicate myogenic vascular function [8,9]. Low frequency fluctuations (LF, 0.04-0.15Hz) indicate the sympathetic nervous activities, and high frequency fluctuations (HF, 0.15-0.4Hz) indicate parasympathetic nervous activities and the release of endothelial-derived nitric oxide [3].…”
Section: Introductionmentioning
confidence: 99%